Pengaruh Instagram (Jejaring Sosial) Terhadap Perilaku Keagamaan Mahasiswa Komunikasi Penyiaran Islam Universitas Islam Negeri Imam Bonjol Padang - Yummil Hasan; Cici Pramida; Usman Usman; Hermawati Hermawati (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2022)
The increasing number of social media users makes it easier for users to interact online in a fast and unlimited time and makes users feel at home to communicate in cyberspace for a long time, especially during adolescence. The effect of the Instagram social network is seen in the religious behavior of the Imam Bonjol Padang State Islamic University (UIN) students. Based on the facts above, the researcher wants to find out more about the influence of the Instagram social network on adolescent religious behavior among students, Faculty of Da'wah and Communication Studies, Imam Bonjol State Islamic University, Padang. Where this research uses quantitative methods and the type of research based on the aspect of the research place is the type of field research and the technique of collecting data is simple random sampling. The results of the research from hypothesis testing show that the better the influence of the Instagram social network, the better the religious behavior of adolescents. This can be seen in the example of the influence, aspects of mental and spiritual development, namely spiritual evolution, aspects of emotional development, namely lack of respect for each other, aspects of social development, namely lack of interaction, including aspects of moral development, namely neglect of time, and aspects of attitudes and preferences that tend to imitate. attitude.